The Genesis of a New Profession: Athletic Academic Counseling - Serrano, Alejandro (My University, 1988)
This article reviews a brief history of the NCAA, changes in college athletics, and the establishment of N4A. At the time of this article, N4A was working to become a non-profit organization, develop a code of ethics, and create a certification program. The author argued for streamlined work environments across institutions, a national communication network of support for people in athletic advising roles, and the need for recognizition by institutions so they have professional credibility and respect to do their jobs accordingly.
Keywords: N4A; ethics